Valence tautomerism induced nucleophilic ipso substitution in a coordinated tetrabromocatecholate ligand and diverse catalytic activity mimicking the function of phenoxazinone synthase - Panja, Anangamohan
Two new manganese(III) complexes, [pyH][Mn(Br(4)Cat)(2)(PY)1 (1) and [Mn(Br(4)Cat)(Br(3)PYCat)(PY)(2)] (2), where py is pyridine, Br(4)CatH(2) is tetrabromocatechol and Br(3)pyCatH(2) is 3,5,6-tribromo-4-pyridiniumcatechol, derived from redox 'noninnocent' bromo-substituted catecholate ligands are reported. Both complexes were characterized by various spectroscopic techniques in addition to the single crystal X-ray crystallography, and the electrochemical behavior of these complexes was investigated by cyclic voltammetry. Variable temperature UV-vis spectral studies for complex I reveal an unprecedented observation in which a dramatic increase of the ligand-to-metal charge transfer band at 592 nm associated with concomitant change in color of the solution from olive-green to dark-green is noticed with increase in temperature. This unprecedented spectral feature is consistent with the formation of a new species 2 in which valence tautomerism induced aromatic nucleophilic substitution of a tetrabromocatecholate ligand by pyridine is observed. DFT calculations have been used to rationalize this unexpected result. To the best of our knowledge, the nucleophilic aromatic substitution of tetra-bromosemiquinone by pyridine to generate this pyridinium-containing catecholate ligand is the first example of valence tautomerism induced nucleophilic ipso substitution by a nitrogen containing ligand. Although the electrochemical behavior of both complexes is similar, the probable role of a positive charge on the ligand backbone has been discussed in order to justify the significantly higher catalytic activity of complex 2 over complex 1. (C) 2015 Elsevier B.V. All rights reserved.